Protection Of Woman Reproductive Rights Laws (Compared Kuhp To Qanun Aceh No. 6 /2014 On Jinayat Law ) - Hesti Kartika Asmara; Kuswardani Kuswardani (Prosiding University Research Colloquium, 2021)
The function of criminal law are to organize social order and to protect individual rights.The aim of the study to describes that the protection against women’s reproductive rightsbetween Criminal Code and Qanun Jinayah by comparing. The study is normativeresearch, so the main data is obtained from library research. Data in the form ofreferences, journals and legal documents. The result show that both regulations provideprotection for women’s reproductive rights. However, the regulations have differenceswhich is seen from (1) actins aspects, imprisonment and terminology. The novelty of thisstudy is that criminal sanctions for assault against women's reproductive rights are notonly in the form of imprisonment but can be in the form of other sanction, such as fine,and compensation.